2019
DOI: 10.1136/bmjopen-2018-025502
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study protocol for the Arabic Healthy Weight Project promoting active living and healthy eating among Arabic-speaking communities in South Western Sydney

Abstract: IntroductionThe South Western Sydney Local Health District (SWSLHD) is home to nearly 75 000 Arabic-speaking people. Of these, nearly three quarters are overweight or obese and suffer from a range of chronic diseases. To address this, the Health Promotion Service of SWSLHD will conduct a community-based overweight and obesity prevention intervention (Arabic Healthy Weight Project, 2018–2021) with Arabic community members aged between 18 and 50 years. The intervention’s main activities will include a comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…For example, it has been reported that they are usually not provided with sufficient information regarding appropriate medication use [28]. Furthermore, few disease self-management interventions have been tailored to enable their application to be adapted to ethnic minority patients [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that they are usually not provided with sufficient information regarding appropriate medication use [28]. Furthermore, few disease self-management interventions have been tailored to enable their application to be adapted to ethnic minority patients [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…This study was approved by the Human Research Ethics Committee of South Western Sydney Local Health District (HREC/16/POOL/303). The details of the study protocol have been reported elsewhere 22…”
Section: Methodsmentioning
confidence: 99%